Body Mass Index Affects Connexin43 Remodeling in Patients with Atrial Fibrillation - Rothe, Susanne; Busch, Andrea; Bittner, Hartmuth; Kostelka, Martin; Dohmen, Pascal Maria; Mohr, Friedrich-Wilhelm; Dhein, Stefan (The Thoracic and Cardiovascular Surgeon, 2014)
Background Increased body mass index (BMI) is often found to be a risk factor for cardiac disease. However, it is unclear whether BMI also affects the gap junction remodeling process in atrial fibrillation (AF). The aim of the study was to see if BMI can influence the connexin43 (Cx43) distribution in patients with sinus rhythm (SR) and AF.Methods We investigated a total of 51 white Caucasian patients of both gender (mean age: 69 years, 30% diabetes mellitus, ejection fraction [EF] > 50%) with SR or AF, with either BMI < 27 or ≥ 27 undergoing cardiac surgery for mitral valve repair, aortic valve repair, or coronary heart disease. We obtained human right atrial tissue for immunohistochemistry and investigated the CX43-positive polar and lateral membrane length in the different BMI (BMI < 27, BMI ≥ 27) and rhythm groups (SR or AF).Results In lean SR patients, Cx43 (BMI < 27) was found mainly at the cell poles while only 2% of the lateral membrane stained positive for Cx43. In obese SR patients (BMI > 27), 6.7 ± 0.7% of the lateral membrane was positive (p < 0.05). In AF generally, there was significantly more lateral Cx43 staining, which was significantly enhanced in obese AF patients. In lean AF patients, lateral Cx43 positivity increased to 14 ± 1% (p < 0.05), while in BMI > 27 AF patients, this was significantly enhanced to 22 ± 2% (p < 0.05). The BMI effect was independent from left atrial diameter, EF, and comorbidity.Conclusions Enhanced BMI is associated with increased remodeling effects of AF on irregular Cx43 distribution.
Keywords: body mass index; atrial fibrillation; remodeling; connexin; gap junctions